2017
DOI: 10.1073/pnas.1706951114
|View full text |Cite
|
Sign up to set email alerts
|

Rewriting nature’s assembly manual for a ssRNA virus

Abstract: SignificanceViruses composed of a shell of coat proteins enclosing ssRNA genomes are among the simplest biological entities. Their lifecycles include a range of processes, such as specific genome encapsidation and efficient capsid self-assembly. Until recently, these were not linked, but we have shown that many viruses in this class encode multiple, degenerate RNA sequence/structure motifs that bind cognate coat proteins collectively. This simultaneously ensures specific genome packaging and efficient virion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 41 publications
0
55
1
Order By: Relevance
“…Engineering of AaLS Protein and Its mRNA. Several ssRNA viruses employ genome packaging strategies that rely on direct interactions between arginine-rich motifs (ARMs) on the viral capsid and specific RNA structures in their genome (15)(16)(17). To equip AaLS capsids with ARMs, we relocated the N and C termini of the individual subunits from the exterior to the interior of the cage, between residues 84 and 85, by circular permutation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Engineering of AaLS Protein and Its mRNA. Several ssRNA viruses employ genome packaging strategies that rely on direct interactions between arginine-rich motifs (ARMs) on the viral capsid and specific RNA structures in their genome (15)(16)(17). To equip AaLS capsids with ARMs, we relocated the N and C termini of the individual subunits from the exterior to the interior of the cage, between residues 84 and 85, by circular permutation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This means that 30-segmentation at the second packaging stage is mainly associated with G+C-rich periodic patterns. The significant harmonics in the vicinity of n = 60 in A+T DFT spectrum may be related to AS suggested by Patel et al (2017). The two-stage transition shown in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…13. Patel et al (2017) suggested for the first assembly stage the motifs AN 2 A. One-to-one correspondence between these motifs and coat proteins implies 60segmentation with A+T-rich patterns. The data by Larson et al (2014) unambiguously assign the strikingly pronounced harmonic at n = 30 (G+C, DFT) in Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has become increasingly appreciated in recent years that for single-stranded RNA viruses, the life cycle is in part regulated by the secondary and tertiary structures of their genomes, hence the current high priority to understand protein-(single-stranded) RNA recognition motifs and RNA sequence-specific folding as it occurs in assembled virions (22,(31)(32)(33)(34)(35). Such information may help with efforts to inhibit viral propagation as well as in nanotechnology applications aimed at harnessing either virus or virus-like systems for efficient gene delivery (36).…”
Section: Discussionmentioning
confidence: 99%